2017
DOI: 10.1167/tvst.6.4.2
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability, Validity, and Normative Data of Interpupillary Distance and Pupil Diameter Using Eye-Tracking Technology

Abstract: PurposeThe purpose of this study was to determine the reliability of interpupillary distance (IPD) and pupil diameter (PD) measures using an infrared eye tracker and central point stimuli. Validity of the test compared to known clinical tools was determined, and normative data was established against which individuals can measure themselves.MethodsParticipants (416) across various demographics were examined for normative data. Of these, 50 were examined for reliability and validity. Validity for IPD measured t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…Eye movements were evaluated with a commercially available eye tracker (RightEye) consisting of a 24-inch 3-dimensional vision monitor fitted with a System Management Interface 12-inch remote eye tracker (NVIDIA) connected to a gaming system (Alienware) and a wireless keyboard and mouse (Logitech). 38 The eye tracker has a 120 Hz temporal resolution and an accuracy of 0.4°. The testing procedure lasted 12 minutes and produced 42 variables related to SPEM, saccades, dynamic visual acuity, and reaction time (eTable 1 in the Supplement ).…”
Section: Methodsmentioning
confidence: 99%
“…Eye movements were evaluated with a commercially available eye tracker (RightEye) consisting of a 24-inch 3-dimensional vision monitor fitted with a System Management Interface 12-inch remote eye tracker (NVIDIA) connected to a gaming system (Alienware) and a wireless keyboard and mouse (Logitech). 38 The eye tracker has a 120 Hz temporal resolution and an accuracy of 0.4°. The testing procedure lasted 12 minutes and produced 42 variables related to SPEM, saccades, dynamic visual acuity, and reaction time (eTable 1 in the Supplement ).…”
Section: Methodsmentioning
confidence: 99%
“…Considering the comparison of the IPD results, the mean IPD of the Azerbaijani population was greater than that of the Turkish population and was also generally greater than that of other populations [9,10,12,17,19,21].…”
Section: Discussionmentioning
confidence: 84%
“…Other optical tools that can be used to measure IPD include 3D digital photoshoots, the Optical Vernier PD Ruler (Fig. 3), and infrared eye trackers [8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The research found a mean pupil diameter of 5.39 ± 1.04 mm at 0 cd/m 2 , 5.20 ± 1.00 mm at 0.5 cd/m 2 , 4.70 ± 0.97 mm at 4 cd/m 2 , 3.74 ± 0.78 mm at 32 cd/m 2 , and 2.84 ± 0.50 mm at 250 cd/m 2 and decreasing pupil size with increasing age. Moreover, a different research evaluated reliability of pupil diameter measurement in 416 healthy participants across diverse demographics with the mean age of 42 ± 8.7 years and the age range from 18 to 73 years (39). The research used an infrared eye tracking technique with a 2D monitor with 85 cd/m 2 luminance in a room at 344 cd/m 2 luminance level, revealing that the mean pupil diameter was 3.53 ± 0.26 mm for right eye and 3.54 ± 0.28 mm for left eye and that the test-to-test reliability was strong.…”
Section: Pupillary Responsementioning
confidence: 99%